Design, Synthesis, and Biological Evaluation of Peptidomimetic N-Substituted Cbz-4-Hyp-Hpa-Amides as Novel Inhibitors of Plasmodium falciparum - Bacherikov, Valeriy A (My University, 2017)
A new series of peptidomimetic N-substituted Cbz-4-Hyp-Hpa-amides were designed, synthesized, and evaluated for inhibition of the Plasmodium falciparum. Substituents on the N-atom of the amide group were selected alkyl-, allyl-, aryl-, 2-hydroxyethyl-, 2-cyanoethyl-, cyanomethyl-, 2-hydroxyethyl-, 2,2-diethoxyethyl-, or 2-ethoxy-2-oxoethylamino groups, and about of 40 new compounds were synthesized and evaluated for antiplasmodial activity in vitro. Antimalarial activity has been investigated as for the final peptide mimetics, and their immediate predecessors, carrying TBDMS or TBDPS protecting groups on 4-hydroxyproline residue and 18 derivatives exhibited toxicity against P. falciparum. Of these agents, compound 23e was shown to have potent antimalarial activity with IC50 528 ng/ml.
Bacherikov Valeriy A. Design, Synthesis, and Biological Evaluation of Peptidomimetic N-Substituted Cbz-4-Hyp-Hpa-Amides as Novel Inhibitors of Plasmodium falciparum / Valeriy A. Bacherikov, Amar Chittiboyina, Mitchell Avery // Chemistry & Biodiversity. – 2017. – Volume 14, Issue 8. – P. 1с. DOI: 10.1002/cbdv.201700037
Keywords: Antimalarial activities; Drug design; Falcipain; Peptidomimetics; Synthesis